Towards climate-smart agricultural policies and investments in Telangana - Kumar, Shalander; Murthy, Dakshina.K; Gumma, Murali K.; Khan P, Elias; Khatri-Chhetri, Arun; Aggarwal, Pramod K.; Murthy, CSR; Chakravarthy, K; Whitbread, Anthony M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
This briefing note summarizes the key findings of the “Scaling up climate-smart agriculture in the Telangana State” project, carried out by the International Crops Research Institute for the Semi-Arid Tropics and partners, between 1st January 2016 and 31st December 2017.